DUKUNGAN MODA TRANSPORTASI UDARA DALAM PENGEMBANGAN KAWASAN INDUSTRI BULI KABUPATEN HALMAHERA TIMUR - Muhammad Rizal; Firdawaty Marasabessy; Edward Risky Ahadian; Siti Aulia Ramadhani (Fakultas Teknik Universitas Khairun, 2018)
District East Halmahera in North Maluku, is district now become one of industrial estatewhich was developed by Ministry of Industry. A Plan to make as one of Industrial area andthis thing also had an influence on the performance of the air transportation, in the Buliairport on East Halmahera which currently categorized as class iii airport with kind of aircraftoperating of ATR 72-600 so that is considered need to be improved the ability of its service inorder to statisfy the demand for which it will follow and also have economic growth andregional development. The purpose of this research to know the number of passengers who willuse the Buli Airport in the year 2032, know the number of the frequency of flight in the year plansuch as in 2032. And knowing the dimension of the airside facilities include the runway, taxiway,and apron in accordance with plan of the Boing 737-500. From the data obtained we could predictat a later date how can the forecasting and demand that will happen. From the data can wereanalysed by using three (3) method of analysis as Linear trend, Kuadratis, and Exponensial. Andfrom the result of the analysis taken the best trend based on the Sum Of Square Error (SSE) toestimate the number of passenger as many as 50548 soul. While obtained the number of planes asmany as 861 a plane with the movement of as much as two the movement of daily. The result pointsto the need to design the addition of runway being 2600m, taxiway 152 x 15 m, and sidening of anapron 105 x 67 m. The result of design inclosed.